ESP Textbook: What the Users' Need? - Sitta Meinawati; Furaidah Furaidah; Johannes Ananto Prayogo (Jurnal Pendidikan Humaniora, 2021)
Abstract: This study was implemented in a private institution focusing on the ESP textbook employed in the class of management. There were 196 students, 9 ESP instructors, and one ESP expert who participated in this research. The aim was to know their perspectives toward the textbook used. It focused on five criteria applied. There were aims and approaches, skills and strategies, topics, practical considerations, and methodologies. The subjects agreed that from criteria of the aims and approaches, topics, and methodologies were good. In contrast, the other criteria, such as practical consideration and skills and strategies, slightly needed to be re-evaluated as some parts of them were inappropriate specifically to their level of comprehension.Keywords: ESP textbook, textbook evaluation, needs analysisAbstrak: Penelitian ini dilaksanakan pada sebuah institusi swasta yang berfokus pada buku ESP yang digunakan pada kelas manajemen. Ada 196 mahasiswa, 9 instruktur dan seorang ahli ESP yang ikutserta dalam studi ini. Tujuannya adalah untuk mengetahui perspektif mereka terhadap buku yang digunakan. Penelitian ini berfokus pada lima kriteria. Kriteria tersebut yakni tujuan dan pendekatan, kemampuan dan strategi, topik, pertimbangan praktis, dan metodologi. Semua subjek setuju bahwa pada kriteria tujuan dan pendekatan, topik, dan metodologi, buku ini sudah baik. Sedangkan kriteria lain seperti pertimbangan praktis, dan keterampilan serta strategi sedikit perlu dievaluasi kembali karena beberapa bagian di antaranya tidak sesuai khususnya dengan tingkat pemahaman mereka. Kata kunci: buku teks ESP, evaluasi buku teks, analisis kebutuhan